1995
DOI: 10.1056/nejm199512143332402
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Heparin for the Treatment of Acute Ischemic Stroke

Abstract: For patients with ischemic stroke treated within 48 hours of the onset of symptoms, low-molecular-weight heparin was effective in improving outcomes at six months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(48 citation statements)
references
References 28 publications
0
47
0
1
Order By: Relevance
“…Angiotensin‐converting enzyme inhibitors or angiotensin II receptor blockers could have some benefit in term of improved survival at 1 year 3. β‐Blockers showed no effect on survival and recurrence rate,3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38 whereas calcium antagonists could be used if coronary vasospasm has been proven during coronary angiogram or with acetylcholine test 32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotensin‐converting enzyme inhibitors or angiotensin II receptor blockers could have some benefit in term of improved survival at 1 year 3. β‐Blockers showed no effect on survival and recurrence rate,3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38 whereas calcium antagonists could be used if coronary vasospasm has been proven during coronary angiogram or with acetylcholine test 32…”
Section: Discussionmentioning
confidence: 99%
“…Current literature shows a higher risk of brain hemorrhage if OAC therapy is started in the first 48 hours after stroke 33, 34. Therefore, OAC therapy could be started between 48 hours and 15 days after ischemic stroke, taking into account the clinical severity, extent of neuroimaging lesions, the risk of cardioembolic recurrence, and risk factors for hemorrhagic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…During the last 3 years four trials of anticoagulation in acute ischemic stroke have been reported in final [1, 2, 3]or preliminary [4]form. Only one of these studies [1]was able to demonstrate that active treatment was better than placebo in improving clinical outcome after ischemic stroke.…”
Section: Recent Heparin Trials: a Frustrating Experiencementioning
confidence: 99%
“…The long-standing controversy concerning the role of heparin in acute stroke was reignited when the Fraxiparine in Stroke Study (FISS) [8]revealed that early treatment with high-dose nadroparin calcium was associated with a 31% (95% confidence interval [CI]: 10–46%) reduction in death or dependency at 6 months, compared with placebo (45 vs. 65%). The results were not conclusive, however, because the treatment groups were not balanced (by chance, the placebo group had more patients with severe stroke), outcome at 3 months after stroke was not significantly different, and the number of outcome events was small, and thus statistically unstable.…”
Section: Emerging Conceptsmentioning
confidence: 99%